Membaca Undang-Undang Nomor 44 Tahun 2008 Tentang Pornografi dari Perspektif Sosiologi Hukum - Murdan Murdan (Indonesian Journal of Shariah and Justice, 2021)
As a society known for its rich tribes, cultures, enis, groups, languages, islands, and so on, it is natural that Indonesia is said to be one of the countries on the world's most multicultural planet. The passing of Law No. 44 of 2008 on Pornography as a hard success among Islamism penetrated the national legislation of Indonesia. As a result, the group of people who disagreed and disagreed with the passage of Law No. 44 of 2008 made various resistance efforts to overturn the Law. The resistance they make from protests through demonstration movements, politics, economics, to efforts to take legal routes. As a result, to this day the Law is only as a documentation of Indonesia's national legislation, and almost no longer gets the attention of the public and law enforcement in Indonesia. In connection with that, this paper will read the existence of Law No. 44 of 2008 on Pornography in the perspective of legal sociology, both in the discussion of legal science in general and in discussions of Islamic-Sharia law.